First Record of Eurasian Spoonbills Platalea leucorodia feeding on Branchiopoda in a temporary wetland (Avocetta, 2020)
The diet of the Eurasian Spoonbill Platalea leucorodia is poorly documented with only the most common prey groups known, namely small fishes, amphibians, reptiles, crustaceans, molluscs, worms, leeches and plant material. Here, three small crustaceans, Branchiopoda Triops cancriformis (Notostraca), Chirocephalus diaphanus (Anostraca), and Cyzicus tetracerus (Spinicaudata) are documented as prey of the Eurasian Spoonbill in a temporary wetland near the San Teodoro salt pan (Marsala, western Sicily). These observations provide a new insight into the foraging ecology of the species, showing its extreme opportunism in targeting small prey when feeding in a temporary wetland system.
Keywords: Triops; Notostraca; Anostraca; Spinicaudata; foraging; western Sicily